The Future of Motherhood in Western Societies
XII, 222 p.
Keywords: iMost couples wish to have children, but when is the best time to have the first child and when is postponement justified? The answers vary from couple to couple and involve many factors including conflicting goals of the parents, housing, career paths, income, parental leave policies and child care arrangements. Nonetheless, the biological clock never stops ticking, and assisted reproductive technology cannot guarantee a successful outcome. This book offers a holistic overview of the process of postponement and its background in modern Western societies both at the personal and societal levels. It includes contributions from reproductive, evolutionary biological and neurological sciences as well as from the fields of demography, economics, sociology and psychology. It argues that governments could support couples by a cafeteria-like set of arrangements from which one can compose a package according to personal preferences that can facilitate to a break in the rising age of first motherhood.